Analysis of High-Intensity Skating in Top-Class Ice Hockey Match-Play in Relation to Training Status and Muscle Damage. Issue 5 (May 2018) - Lignell, Erik; Fransson, Dan; Krustrup, Peter; Mohr, Magni
Abstract : Abstract: Lignell, E, Fransson, D, Krustrup, P, and Mohr, M. Analysis of high-intensity skating in top-class ice hockey match-play in relation to training status and muscle damage. J Strength Cond Res 32(5): 1303–1310, 2018—We examined high-intensity activities in a top-class ice-hockey game and the effect of training status. Male ice-hockey players ( n = 36) from the National Hockey League participated. Match analysis was performed during a game and physical capacity was assessed by a submaximal Yo-Yo Intermittent Recovery Ice-hockey test, level 1 (YYIR1-IHSUB ). Venous blood samples were collected 24-hour post-game to determine markers of muscle damage. Players performed 119 ± 8 and 31 ± 3 m·min −1 of high intensity and sprint skating, respectively, during a game. Total distance covered was 4, 606 ± 219 m (2, 260–6, 749 m), of which high-intensity distance was 2042 ± 97 m (757–3, 026 m). Sprint-skating speed was 5–8% higher ( p ⩽ 0.05) in periods 1 and 2 vs. period 3 and overtime. Defensemen (D) covered 29% more ( p ⩽ 0.05) skating in total than forwards (F) and were on the ice 47% longer. However, F performed 54% more ( p ⩽ 0.05) high-intensity skating per minute than defensemen. Plasma creatine kinase (CK) was 338 ± 45 (78–757) U·L −1 24-hour post-game. Heart rate loading during YYIR1-IHSUB correlated inversely ( p ⩽ 0.05) to the frequency of high-intensity skating bouts ( r = −0.55) and V[Combining Dot Above]O2 max ( r = −0.85) and positively to post-game CK ( r = 0.49; p ⩽ 0.05). In conclusion, ice hockey is a multiple-sprint sport that provokes fatigue in the latter half of a game. Forwards perform more intense skating than defensemen. Moreover, high-intensity game activities during top-class ice hockey are correlated with cardiovascular loading during a submaximal skating test. Taken together, training of elite ice-hockey players should improve the ability for repeated high-intensity skating, and testing should include the YYIR1-IHSUB test as an indicator for ice-hockey–specific physical match performance.